Organizational Methods of Furniture and Their Aesthetic Relationships in Interior Design - Akram Faraedon Hamaamen; Alwand Dlshad Najib (Zanco Journal of Humanity Sciences)
Different styles appeared in the design of furniture and its aesthetic organization in the interior space and one of the most prominent styles and movement that emerged in the time of modernity in the year (1914-1880) art novo movement, a French word meaning new art, an international style of art, architecture and design that reached the peak in popularity at the beginning of the twentieth century and characterized by very renewable designs, In 1931-1917, the De Steele movement emerged, and De Steele distinguished itself from others with types of abstract art in the use of geometric shapes and composite constructions. In 1933-1919, the Bauhaus School emerged and is considered one of the most important intellectual methods of supporting modern thought, where it presented in its buildings and the arrangement of its space and furniture organizations a model of simplicity in form, mass and size and the fact that it gives dazzle and beauty, and returns the design to geometric shapes, and in a year(1940-1920) The Art Deco movement emerged as one of the methods of the trend of modernity in design, and then different styles and trends emerged in the mid-1960s and early 1970s and was named after postmodernism, one of its most prominent pioneers Robert Venturi, the famous saying "Less is Bore" that supports chaos and complexity, as opposed to the theory of architect Ms. Van Droh "less is more". In the 20th century, the styles were launched from the movement and contemporary trends and were characterized by many scientific and technological events that had a direct impact on aesthetic relationships in the form of architecture and interior space and then the design of furniture and styles, most notably abstract and dismantling, and pop art.